Pemanfaatan Cangkang Telur Ayam Sebagai Pupuk Organik diDesa Ombulodata Kabupaten Gorontalo Utara - Siswatiana Taha; Muhamad Mukhtar; Syukri I Gubali; Srisukmawati Zainuddin (Jambura Journal of Husbandry and Agriculture Community Serve (JJHCS), 2022)
This service will be addressed to the residents of Ombulodata Village, Kwandang District, North Gorontalo Regency. Several activity programs have been carried out at the location of the activity, namely the Introduction and Processing of Eggshell Waste into Organic Fertilizer, Eggshell Waste Collection, Eggshell Waste Processing into Flour, and Organic Fertilizer Production. The method used in empowering the target partner group is a learning technique in the form of providing theory and simulation to village residents who are target partners and then direct practice with students and villagers. Ombulodata village has the most agricultural land compared to other villages in Kwandang sub-district. the local government provides assistance in the form of more fertilizer to each farmer group. but often insufficient and even damage the plant. Another potential possessed by Ombulodata village is, if you observe the area around Ombulodata village, the availability of land with fruit, chili and tomato plants is quite a lot